Indigenous Energy Justice: Multitemporalities, Natural Law, and Decolonial Governance in Anishinaabeg Pipeline Resistance - Awasis, Sakihitowin (Scholarship@Western, 2023)
From Standing Rock to Unist’ot’en, battles over proposed oil and gas pipeline projects are mounting across Turtle Island (North America). Given the level of colonial violence surrounding these projects and the tensions that arise from diverse worldviews conflicting in decision-making, there is an urgent need to better understand Indigenous law on its own terms, not framed by colonial legal systems. To do this, I focus on two case studies in Anishinaabe Akiing (territory), Line 9 (Sarnia, Ontario to Montréal, Québec) and Line 3 (Hardisty, Alberta to Superior, Wisconsin). I ask what is Indigenous energy justice? What does it look and feel like to Anishinaabe people engaged in pipeline resistance? To answer these questions, I take a decolonizing approach to process tracing techniques including document analysis, participation in community life, and in-depth interviews while visiting with Anishinaabe pipeline opponents. This dissertation is divided into three papers rooted in Anishinaabe ways of living and multiple temporalities that have been largely supplanted by a single, linear colonial temporality. The first paper begins by considering tensions between Anishinaabe and settler temporalities reflected in the 2012-17 Line 9 pipeline dispute. While colonial temporal modes result in narrower and more short-sighted project reviews, Anishinaabe temporalities open possibilities for Indigenous self-determination in energy decision-making. In the second paper, I examine one of these possibilities further. I explore how traditional harvesting protocols can be applied to energy governance, focusing on the Line 3 expansion plan. I identify four overlapping key concepts: rights, responsibility, relationality, and reciprocity. These principles are then mapped onto Anishinaabe understandings of oil, hydro, wind, and solar energy. The resulting analysis challenges extractivist narratives of energy production and provides an opportunity to rethink the relationship between people and energy. The last paper describes decolonial ...